Long term benefit of a targeted diabetes education program: the KK Chini experience - Kamaruzaman, Nor Azam; Pasi, Hafizah; Bakar, Bustamanizan; Z, Asyikin (Academy of Family Physicians of Malaysia (AFPM), 2021)
An effective diabetes education may empower the patient in reinforcing self-care and a healthy lifestyle. We aim to evaluate the one-year outcome of an education program on a targeted group of diabetic patients at a primary health clinic. This is a cohort survey recruiting poorly controlled diabetic patients into a locally designed education program at KK Chini, Pahang. The cohort of 37 patients participated in 2017 and 2018 with complete record were included in this study. All relevant diabetes management information before and one year after the program were obtained and analysed using SPSS 24.0 version.